Establecimiento de un sistema piloto para tratamiento de aguas grises domésticas empleando fibra de coco en la comunidad “JABONCILLO”, Parroquia Picoazá - Ramírez Olives, Ramón Andrés (2023)
The objective of this investigation was to establish a pilot system for the treatment of domestic gray water using coconut fiber in the "Jaboncillo" community, Portoviejo, Manabí - Ecuador. This study was of a qualitative experimental type with a completely randomized design, with a 2x3 bifactorial arrangement, resulting in 6 treatments, with 6 repetitions, obtaining a total of 36 experimental units plus a control treatment (conventional filter without coconut fiber). The results indicate that the domestic wastewater they generate is not suitable for agricultural use but, with effective treatment, they can be reused. The raw water to be filtered had 11,200 mg/L of COD and 3,000 mg/L of BOD5, without significant differences for the parameters of turbidity, SDT, TSS by treatments (p-value > 0.05), but in terms of pH. (T5 and T6 < 0.05); while in the repetitions significant differences were found for turbidity, SDT and TSS (p-value < 0.05) but not for pH (T1 to T5 p-value > 0.05). The filter corresponding to treatment 2 (30g powdered fiber + 60g trimmed fiber) had the best efficiency (27.93%); while treatments 3 and 4 had efficiencies of less than 2%. The proposed hypothesis is rejected because the coconut fiber-based filter removed 27.93% of organic matter from Jaboncillo's gray water and the removal goal was 50%. The cost of production and implementation of the filter with the best treatment (T2) was $150.00.